2020
DOI: 10.22329/jtl.v13i2.5971
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Upper Secondary School Students’ Perceptions of Their Teachers’ Assessment Practices

Abstract: The paper addresses Finnish students’ perceptions of assessment practices in upper secondary school. We study what experiences students have about assessment, and how they assess their ability to use and understand teachers’ feedback. The data were gathered on a web-based questionnaire to 918 students in four upper secondary schools. The questionnaire contained both closed-ended and open-ended questions. According to students’ responses, most students consider that they are able to use and understand their tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…Additionally, Finnish students associated assessment with teacher-oriented assessment practices, their responses ranging from teacher feedback to exams made by the teacher (Table 2). This finding seems to agree with previous studies exploring Finnish students' perceptions of assessment, in which assessment was still considered traditional and primarily led by the teacher (Hildén and Härmälä 2015;Mäkipää and Ouakrim-Soivio 2020). Pollari (2016) and Tarnanen and Huhta (2008) also indicated that classroom-based assessment is apparent both in primary and secondary Finnish education.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, Finnish students associated assessment with teacher-oriented assessment practices, their responses ranging from teacher feedback to exams made by the teacher (Table 2). This finding seems to agree with previous studies exploring Finnish students' perceptions of assessment, in which assessment was still considered traditional and primarily led by the teacher (Hildén and Härmälä 2015;Mäkipää and Ouakrim-Soivio 2020). Pollari (2016) and Tarnanen and Huhta (2008) also indicated that classroom-based assessment is apparent both in primary and secondary Finnish education.…”
Section: Discussionsupporting
confidence: 91%
“…Self-assessment was associated with learner autonomy and feedback. Even though feedback has been associated as teacherled in Finland (Hildén and Härmälä 2015;Mäkipää and Ouakrim-Soivio 2020), interestingly in this study, the students did not present a hierarchical order of feedback, e.g., from the teacher to the students. Instead, their idea of feedback was circular via collaboration of all classroom entities since everyone in the classroom could provide feedback.…”
Section: Discussioncontrasting
confidence: 52%
“…The results suggest that teachers give feedback particularly on errors and improvement, but the students reported a lack of feedback, especially concerning oral feedback. Research has also stressed this lack of feedback in Finnish schools (Atjonen et al, 2019;Mäkipää & Ouakrim-Soivio, 2019). Students' perceptions differ significantly from those of the teachers as they pointed out that they had given a lot of oral feedback during the lessons.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers also mark the errors comprehensively -usually with a correction or an explanation, but occasionally also without any clarification (Atjonen et al 2019;Mäkipää 2021b). All in all, when compared to the stipulations of the latest Finnish National Core Curricula (FNBE 2016;FNAE 2019), the amount of formative feedback seems low (e.g., Atjonen et al 2019;Mäkipää & Ouakrim-Soivio 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, learners are predominantly more or less passive recipients of assessment and feedback. Although learners are well informed of the assessment practices and criteria at the beginning of each course by the teacher (Välijärvi et al 2009;Atjonen et al 2019;Mäkipää & Ouakrim-Soivio 2019), their role in influencing the decisions may be rather limited (Pollari 2017a), and they may not always understand what the criteria mean (Mäkipää 2021a). Self-and peer-assessment are used to a degree but do not appear to have an established role in classroom assessment (Mäkipää 2021a;Leontjev, 2022).…”
Section: Introductionmentioning
confidence: 99%